Engineering the Immune Response to Biomaterials - Abolfazl Salehi Moghaddam; Mehran Bahrami; Einollah Sarikhani; Rumeysa Tutar; Yavuz Nuri Ertas; Faleh Tamimi; Ali Hedayatnia; Clotilde Jugie; Houman Savoji; Asma Talib Qureshi; Muhammad Rizwan; Chima V. Maduka; et al. (Advanced Science)
Abstract Biomaterials are increasingly used as implants in the body, but they often elicit tissue reactions due to the immune system recognizing them as foreign bodies. These reactions typically involve the activation of innate immunity and the initiation of an inflammatory response, which can persist as chronic inflammation, causing implant failure. To reduce these risks, various strategies have been developed to modify the material composition, surface characteristics, or mechanical properties of biomaterials. Moreover, bioactive materials have emerged as a new class of biomaterials that can induce desirable tissue responses and form a strong bond between the implant and the host tissue. In recent years, different immunomodulatory strategies have been incorporated into biomaterials as drug delivery systems. Furthermore, more advanced molecule and cell‐based immunomodulators have been developed and integrated with biomaterials. These emerging strategies will enable better control of the immune response to biomaterials and improve the function and longevity of implants and, ultimately, the outcome of biomaterial‐based therapies.